Spontaneous Ventilation Video-Assisted Thoracoscopic Surgery for Non-small-cell Lung Cancer Patients With Poor Lung Function: Short- and Long-Term Outcomes - Wang, Runchen; Wang, Qixia; Jiang, Shunjun; Chen, Chao; Zheng, Jianqi; Liu, Hui; Liang, Xueqing; Chen, Zhuxing; Wang, Haixuan; Guo, Zhuoxuan; Liang, Wenhua; He, Jianxing; et al. (Frontiers in Surgery, 2022)
Objective: The goal of this study was to explore the feasibility and safety of spontaneous ventilation video-assisted thoracoscopic surgery (SV-VATS) for non-small-cell lung cancer (NSCLC) patients with poor lung function. Methods NSCLC patients with poor lung function who underwent SV-VATS or mechanical ventilation VATS (MV-VATS) from 2011 to 2018 were analyzed. 1:2 Propensity score matching (PSM) was applied, and the short- and long-term outcomes between the SV-VATS group and the MV-VATS group were compared. Results: Anesthesia time (226.18 min ± 64.89 min vs. 248.27 min ± 76.07 min; P = 0.03), operative time (140.85 min ± 76.07 min vs. 163.12 min ± 69.37 min; P = 0.01), days of postoperative hospitalization (7.29 days ± 3.35 days vs. 8.40 days ± 7.89 days; P = 0.04), and days of chest tube use (4.15 days ± 2.89 days vs. 5.15 days ± 3.54 days; P = 0.01), the number of N1 station lymph node dissection (2.94 ± 3.24 vs. 4.34 ± 4.15; P = 0.005) and systemic immune-inflammation index (3855.43 ± 3618.61 vs. 2908.11 ± 2933.89; P = 0.04) were lower in SV-VATS group. Overall survival and disease-free survival were not significantly different between the two groups (OS: HR 0.66, 95% CI: 0.41-1.07, P = 0.09; DFS: HR 0.78, 95% CI: 0.42-1.45, P = 0.43) Conclusions: Comparable short-term and long-term outcomes indicated that SV-VATS is a feasible and safe method and might be an alternative to MV-VATS when managing NSCLC patients with poor lung function.